FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PELAYANAN PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KAUR - Suryani, Raflen (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
Regency Regional Financial and Asset Management Agency is a government organization whose duties are to provide services. Service will be able to satisfy if the service performance provided is of high quality. The importance of quality service is why the author focuses this research on service performance with the factors that will be studied in influencing service are productivity, service quality, responsiveness and accountability. This research is quantitative research with data sources obtained from 30 respondents. The main tool for collecting data is a questionnaire. The data analysis used is quantitative analysis. The results of hypothesis testing using the t test (t-test) obtained that the calculated t value of the four independent variables had a significance < alpha 0.05. The results of hypothesis testing using the F test (F-test) obtained a calculated F value with a significance of <alpha 0.05. Therefore, productivity, service quality, responsiveness and responsiveness partially and simultaneously have a positive and significant effect on service performance at the Regional Financial and Asset Management Agency of Kaur Regency.